Developing a Learning Tool Based on the Problem-Based Learning Model to Improve Students' Problem Solving and Collaboration Skills - Dedi Irawan; Bornok Sinaga; Elmanani Simamora (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to create a learning aid product based on a realistic, practical, effective, and enhanced problem-based learning model to improve the problem-solving and teamwork abilities of eighth-grade students of SMP WR. Supratman 1 Medan. This research technique, developed by Thiagarajan and Semmel, is a learning aid known as the 4-D model (Define, Design, Develop, Disseminate). Class VIIIA students of SMP WR. Supratman 1 Medan in the 2025/2026 academic year became the subject of the study. Valid and practical problem-based learning aids based on the learning aid plan, Student Worksheets, Teacher's Books, and Student Books were found in this study. Students' mathematical problem-solving abilities increased after using problem-based learning on a system of linear equations with two variables, as shown by an average of 86% achievement in the posttest of experiment I and experiment II. Problem-based learning on a system of linear equations with two variables improved students' ability to collaborate mathematically, as evidenced by their average scores in experiments I and II.